GENDER VARIATIONS IN THE PREVALENCE AND CORRELATES OF DEPRESSION AND ANXIETY AMONG ADOLESCENTS IN SOUTH-EASTERN NIGERIA - Nnubia, Uju I.; Emmanuel, Nancy C. (International Journal of Child, Youth and Family Studies, 2024)
This study explored gender variations in the prevalence and correlates of depression and anxiety among Nigerian adolescents. Using a cross-section of 836 students aged 10 to 18 years (39.5% males and 60.5% females), the study determined gender differences in the prevalence of and the demographic, socioeconomic, and lifestyle factors associated with, depression and anxiety among the respondents. Data were collected using a prevalidated questionnaire and the 25-item Revised Child Anxiety and Depression Scale. Analyses were carried out with the SPSS statistical software (version 21); frequencies and percentages, chi-squared statistics, and point-biserial correlations were examined. Results showed a high(35.4%) prevalence of general anxiety and depression among adolescents. Male respondents had a higher proportion of anxiety (32.1%), depression (31.5%), and general anxiety and depression (44.8%) compared to females who had 20.9% symptomatic depression, 21.9% anxiety, and 29.2% general anxiety and depression. Correlates of mental health symptoms in boys were mothers’ education and living with guardians. Having unemployed fathers correlated with anxiety symptoms in girls. Age, class, perceived family socioeconomic status, and emotional connection with parents/guardians were significantly correlated with mental health in both male and female adolescents; however, the pattern of these interactions varied between the genders. Since this study has shown that gender variations exist in the prevalence and correlates of poor mental health among Nigerian adolescents, programs targeting them should reflect gender considerations.